Study guides

☆☆☆☆☆

Q: 2x plus 2x plus 2x equals 6?

Write your answer...

Submit

Still have questions?

Related questions

2x + 3x + 6 = 5x + 6

8x-7 plus 2x equals 6 plus 5x plus 2?

-2x-6= -2x-6Another answer:-2x-6 = 2x+6-2x-2x = 6+6-4x = 12x = -3

2x-11

6y

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

4x+35-2x+25 = 6 2x+60 = 6 2x = 6-60 2x = -54 x = -27

DIE

2x+3=9 2x=9-3 2x=6 2x/2=6/2 X=3

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

2x+2=x+6 first subtract 2x. -2x -2x2=-1x+6 then subtract 6-6 -6-4=-1x finally divide by -1x=4 X equals four.

2x + 1 = 6 2x = 5 x = 5/2 or 2.5

22+2x = 37+6+x 2x-x = 37+6-22 x = 21

2x-6=x+5 x=11

6 + 2x = x - 6 2x - x = -6 -6 x = -12

2x + 3 = -92x = -12x = -6

6 + 2x = x - 6 6 + x = -6 x = -12

2x + 1 = 13; 2x = 12; x = 6

x-2.

7

2x + 4 = 10 2x = 10 - 4 = 6 2x = 6 x = 6/2 = 3

if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7

3x - 3 = 2x + 6 3x = 2x + 9 x = 9

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

2x+8 = 6 2x = 6-8 2x = -2 x = -1